Design And Analysis Of Mechanical Mating Interfaces For Reconfigurable Machine Tools - Maideen, Normariah Che (2010)
Reconfigurable Machine Tools (RMTs) which are designed under modularity concept are a new approach in machine tools technology which is characterized by customized flexibility to serve current production requirements. It allows changes in machine physical configuration whenever required. This concept of machine tools is still under development stage. Even though there are numbers of design methodologies proposed, there is no method specifically mentioned on how each module would be assembled together. Using a structured design approach, the newly design of mechanical mating interface method is proposed. Two non-vertex cones with pin-slot arrangement were found to be the best concept. Using Finite Element Method (FEM), the detail design on the optimum design variables was determined. The stiffer assembly was assured when the ratio of depth of penetration to the total mating interface thickness used is 0.6. The 1/10 tapered angle was the best value for the cones and 0.15 mm of the face clearance between mating interfaces ensured 5μm of interference fit. Using simulation modelling, the performance of the newly designed mating interface was investigated and compared with conventional interface method. The newly designed mating interfaces were confirmed to perform better compared to conventional method. Finally, the tolerance analysis was conducted and appropriate tolerance values were allocated. The intended interference fit of the assembled modules was achieved.